Can Participatory Groundwater Management Enhance Drought Resilience? The Case of the Andhra Pradesh Farmer-Managed Groundwater Systems Project - Reddy, V. Ratna (World Bank, Washington, DC, 2020)
This paper investigates whether the proactive involvement of local communities in the management of groundwater can help build drought resilience, using the case of the Andhra Pradesh (AP) Farmer Managed Groundwater Systems (APFAMGS) project as an example. The 18-year project was implemented through seven districts of India’s AP and Telangana states. During this period, participatory groundwater management (PGM) initiatives evolved from a focus on demand management to an emphasis on drought adaptation as links between groundwater and climate variability became increasingly conspicuous. This paper is based on a review of existing studies, field visits to the region, and interactions with communities and individual farmers. The objective of APFAMGS was to promote sustainable groundwater management by creating community awareness through training, water planning, and alternative cropping choices. The study concludes that PGM, as adopted in APFAMGS, has a limited impact on groundwater levels in hard rock areas under conditions of marginally decreasing rainfall, greatly increasing net abstraction, and groundwater dependency. However, the project improved awareness that helped communities adapt to drought. The conclusion is that to be effective in addressing drought vulnerabilities, PGM must include policy interventions that encompass incentive and regulatory mechanisms, and village-based institutions must be linked to government departments that manage groundwater.